BLOCKCHAIN TECHNOLOGY AS A SOLUTION OF INTEGRATION ISSUE IN HALAL FOOD SUPPLY CHAIN - Andi Ahianindiasdri Sarah; Bettine Bergmans (Diponegoro Journal of Accounting, 2021)
Halal food is an obligation for Muslims to consume. Therefore, Halal food can be consumed when it meets the requirement of Halal certification. However, there are several issues in Halal industry, such as Halal counterfeiting, Halal fraud, Cross-contamination food, etc. One of the most sensitive issues in the Halal industry is the integrity of the food supply chain. The paper provides a conceptual framework for the verification of the halal food chain for processed food products. It is hoped that the framework will assist food industry players in developing a mechanism that will enhance the transparency and legitimacy of the halal food chain. Along with 4th Industrial Revolution era, the emerging technologies provide an ideal solution to the issues currently faced by companies across the world, and one such area is the Supply Chain Management. The issues in the Halal Food Supply Chain can effectively be addressed by the emerging Blockchain Technology.